DECISION SUPPORT SYSTEM FOR PALM PLANTATION LAND SELECTION USING THE TOPSIS METHOD - Nuraini, Rini; Liesnaningsih, Liesnaningsih; Handayani, Nurdiana; Rusdianto, Hengki (Jurnal Pilar Nusa Mandiri, 2022)
Palm oil is an important export commodity in Indonesia. Quality palm oil is produced from quality oil palm plants as well. One of the factors to be able to produce quality oil palm plantations requires the right land. For this reason, land selection is an important factor. This study aims to develop a decision support system by implementing the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) method for the selection of oil palm plantations. The TOPSIS method is a negative approach that is obtained by considering the shortest distance from the positive ideal solution and the farthest from the ideal solution. The system is built using a waterfall system development approach that starts from analysis, design, coding and testing. The developed system has the ability to manage alternatives, manage criteria, perform alternative calculations with TOPSIS, and display the best alternative results with TOPSIS. From the results of black-box testing, it proves that the developed system can work and run well. In addition, the results of manual calculations with the system show the same results.